Strategi Discovery Learning dalam Pembelajaran Anak Usia Dini - Munawarah, Siti (STAIN Bengkalis, 2021)
The current learning paradigm has changed from being teacher-oriented to student-oriented. One of the student-oriented learning strategies is discovery learning. However, there are still many teachers who do not understand the meaning of student-oriented in practice, then the teacher dominates learning in the classroom learning and eliminating the participation of children to be active. This study uses a qualitative approach and the data were collected using the library research technique. In the discovery learning, the teacher designs some problems about learning themes and the students are given the freedom to find their own concepts that will be learned through critical thinking so that become life skills for them. Discovery learning changes the conditions of passive learning into active and creative, the students are given the freedom to explore, actively create, and generalize their knowledge. Through discovery learning strategies, the students are expected to become problem solvers to solve some problems and make decisions.Paradigma pembelajaran saat ini sudah berubah dari yang bersifat teacher oriented menjadi student oriented. Salah satu strategi pembelajaran yang berbasis student oriented adalah discovery learning. Namun, masih banyak pendidik yang belum memahami makna student oriented pada pelaksanaannya, kemudian lebih mendominasi pembelajaran di kelas, sehingga menghilangkan partisipasi anak untuk aktif. Penelitian ini menggunakan pendekatan kualitatif, teknik pengumpulan data yang digunakan adalah studi kepustakaan. Pada strategi discovey learning, guru merancang beberapa masalah tentang tema pembelajaran dan siswa diberikan kebebasan untuk menemukan sendiri konsep-konsep yang akan dipelajari melalui berpikir kritis yang nantinya akan menjadi life skill bagi mereka. Discovery learning merubah kondisi belajar pasif menjadi aktif kreatif, Anak diberi kebebasan untuk mengeksplorasi, aktif menciptakan, dan menggeneralisasi pengetahuannya. Melalui strategi ini anak diharapkan dapat menjadi problem solver, sehingga mampu menyelesaikan masalah dan mengambil keputusan.